Histología del sistema reproductor masculino de Helobdella hyalina (Hirudinea, Glossiphoniidae) en Argentina - Gullo, Bettina Sandra (2004)
A detailed preliminary histological analysis of Helobdella hyalina Ringuelet, 1942 male system from Los Talas, Buenos Aires, Argentina is described. Six pairs of testisacs, located between the crop caeca, form the male reproductive system. Each testisac is clothed by the mesotelium. Inside it, the germinal cells are connected to the citophore and develop functional unit called poliplast. The spermatozoa are released into testisacs after the reabsortion of the citophore. Five stages of spermatogenesis are described taking into account the successive maturation stages of germinal cells and the changes in the citophore size. Lining cells and gland cells were found in the seminal vesicle. Five different types of gland cells are placed inside the ejaculatory ducts, as well as two kinds of cells are found in its distal portion: type 1, which produces eosinophilic granular secretion, type 2, with amorphous and slightly eosinophilic. Three distinct gland cells are located in the proximal portion of the duct: type 3, which produces a strongly eosinophilic granular secretion; type 4, with a negative eosinophilic amorphous secretion and type 5, with a basophilic granular secretion. Type 5 gland cells are described for the ducts of this species only.